West Nile Virus in American White Pelican Chicks: Transmission, Immunity, and Survival - Sovada, Marsha A. (The American Society of Tropical Medicine and Hygiene, 2013)
West Nile virus (WNV) causes significant mortality of American White Pelican chicks at northern plains colonies. We tested oropharyngeal/cloacal swabs from moribund chicks for shed WNV. Such shedding could enable chick-to-chick transmission and help explain why WNV spreads rapidly in colonies. WNV was detected on swabs from 11% of chicks in 2006 and 52% of chicks in 2007; however, viral titers were low. Before onset of WNV mortality, we tested blood from < 3-week-old chicks for antibodies to WNV; 5% of chicks were seropositive, suggesting passive transfer of maternal antibodies. Among near-fledged chicks, 41% tested positive for anti-WNV antibodies, indicating that they survived infection. Among years and colonies, cumulative incidence of WNV in chicks varied from 28% to 81%, whereas the proportion of chicks surviving WNV (i.e., seropositive) was 64–75%. Our data revealed that WNV kills chicks that likely would fledge in the absence of WNV, that infection of chicks is pervasive, and that significant numbers of chicks survive infection.